MIGRASI PENGAJIAN KONVENSIONAL KE PENGAJIAN VIRTUAL DI PESANTREN - Masruroh, Sayidah Afyatul; Muhid, Abdul (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2022)
This article aims to discuss the movement of conventional recitations to virtual recitations in Islamic boarding schools. This article is the research result of a literature review on the transformation of the virtual recitation model through new media in the pesantren scope. This study aims to uncover the adaptation of pesantren toward the development of information and communication technology due to modernization and globalization. Besides, it also focuses on the efforts of pesantren in concerning the culture created by the latest media in pesantren to maintain it. The results of this study indicate that the advancement of information and communication technology in pesantren provides a great opportunity for pesantren to adapt by transforming the recitation system virtually, so that pesantren as a symbol of Islamic civilization is still recognized by modern society as a religious institution. The researcher argues that currently pesantren must open themselves to the advancement of information and communication technology through latest media, so that pesantren graduates are also able to develop Islamic syiar activities by utilizing latest media, which impacts to equip them to compete with global community.